Interpenetration as a Mechanism for Negative Thermal Expansion in the Metal–Organic Framework Cu3(btb)2 (MOF‐14)1. Issue 20 (1st April 2014) - Wu, Yue; Peterson, Vanessa K.; Luks, Emily; Darwish, Tamim A.; Kepert, Cameron J.
Abstract Metal–organic framework materials (MOFs) have recently been shown in some cases to exhibit strong negative thermal expansion (NTE) behavior, while framework interpenetration has been found to reduce NTE in many materials. Using powder and single‐crystal diffraction methods we investigate the thermal expansion behavior of interpenetrated Cu3(btb)2 (MOF‐14) and find that it exhibits an anomalously large NTE effect. Temperature‐dependent structural analysis shows that, contrary to other interpenetrated materials, in MOF‐14 the large positive thermal expansion of weak interactions that hold the interpenetrating networks together results in a low‐energy contractive distortion of the overall framework structure, demonstrating a new mechanism for NTE.